277 Implementation of the ROSA Robot in a DGH. (28th February 2022) - Easwaran, A.; Jones, R.; Easwaran, P.; Kincaid, R.
Abstract: Introduction: The ROSA (Robotic Surgical Assistant) is designed to assist orthopaedic surgeons performing total knee arthroplasty (TKA). It is postulated that the real-time data provided by the ROSA robot aids the surgeon by providing objective values to bone resections and soft tissue balance, enabling better implant selection and positioning. This is thought to improve patient outcomes through reduced post-operative pain, reduced hospital stays and reduced revision rate. To date, the ROSA robot has solely been implemented in tertiary centres in the UK. This study investigates the implementation of the ROSA robot in a district general hospital (DGH) in a geographically isolated region of the UK. Method: The ROSA robot was installed in St. Michael's Hospital, Cornwall in July 2021. Prior to its clinical deployment, six surgeons undertook saw bone training. Following this, six ROSA-assisted TKAs were performed in six weeks between July and August 2021. Logistical challenges to implementation included difficulty in ROSA component delivery given geographical isolation, consultant training time dedicated to ROSA operation in the context of a busy DGH trauma rota and increased operative time during the learning curve. Conclusions: Despite the challenges faced, we have demonstrated that ROSA can be implemented in a rural, geographically distanced DGH. Given the use of robotic assistance in other surgical specialties, this is an exciting prospect for elective knee surgery in the future.